Effect of high-intensity interval training on cardio-metabolic risk markers in adolescents: 3-month follow-up of Project FFAB (Fun Fast Activity Blasts) - Taylor, K.; Azevedo, L.; Bock, S.; Batterham, A. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Project FFAB is an exploratory controlled before and after study of the effects of a practical and engaging low-volume highintensity training (HIT) intervention on cardio-metabolic risk markers. The extent to which adaptations to HIT can be maintained is unknown (Gibala & McGee, 2008). We aimed to evaluate the maintenance of any beneficial intervention effects at 3 months follow-up. Methods: Participants were 102 adolescents (64 male; 14.3 ± 0.3 years; mean ± SD) from four schools; two schools were assigned to the Intervention (n = 41) and two to the Control, matching for socioeconomic status. The intervention comprised four sets of 45 s maximal effort exercise (at least 90% of maximum heart rate) involving boxing, dance, soccer and basketball drills, with 90 s rest between sets, up to three times weekly for 10 weeks. The number of sets was increased by one every two weeks. Outcomes were blood lipids and glucose, waist circumference, C-reactive protein, blood pressure, physical activity levels (7-day accelerometry), aerobic fitness (multistage fitness test), and carotid artery intima-media thickness. The difference in the change from baseline (intervention minus control) was estimated for each outcome, with sex, the baseline value, and maturity offset as covariates. Using magnitude-based inferences (MBI) with qualitative probabilistic descriptors (Hopkins et al., 2009), we calculated the probability (P, MBI) that the true population effect was greater than the minimum important difference (MID; 0.2 standard deviations). Results: Compliance was indicated by 75% of the intervention group completing at least 70% of the sessions. At the post-intervention time point, we had previously observed clinically relevant improvements vs. control (`likely` or `very likely` to be greater than the MID) in triglycerides (-24%), waist circumference (-2.7 cm), and mean daily moderate to vigorous physical activity (MVPA) (14.3 min). At 3-months follow-up the mean triglyceride level was 6% lower in Intervention vs. Control (90% confidence interval, -22 to 14%; P, MBI = 0.38), waist circumference was 2.2 cm smaller (-3.4 to -1.1 cm; P, MBI = 0.43), and mean daily MVPA was 12.8 minutes greater (-12.0 to 37.7 minutes; P, MBI = 0.69). All three effects were `possibly` important. There was no substantial effect on any other outcome. Discussion: Clinically relevant post-intervention effects were attenuated at 3-months follow up. There is some evidence of a possible residual benefit, but exercise interventions must be regular to maintain beneficial adaptations.